What are the limitations of the non-patient-specific implant in titanium reconstruction of the orbit?. Issue 9 (November 2020) - Schlittler, F.; Vig, N.; Burkhard, J.P.; Lieger, O.; Michel, Ch.; Holmes, S.
Abstract: There is ongoing discussion about patient-specific implants (PSI) to reconstruct orbital defects. Although PSI offer excellent clinical outcome, they are expensive. Subsequently, their routine application is not indicated. The purpose of this study was to estimate the frequency of implant malposition and revision procedures after primary orbital repair with preformed plates and to identify cases where primary use of PSI would help to prevent revision surgery. All patients included in the study were operated on for orbital fractures at the Royal London Hospital between August 2017 and July 2018. Selection criteria included adult patients treated for orbital fractures with a titanium plate. Revision was planned in symptomatic patients presenting with clear implant malposition. Seventy-nine patients with 81 implants were included, 33 of whom had multiple orbital wall fractures (medial wall and floor or all four walls) and were summarised as group 2. Group 1 consisted of single orbital floor/medial wall fractures. The five patients for whom revision surgery was planned or undertaken because of radiological poorly positioned implants and substantial clinical symptoms all had multiple wall fractures. This finding was significant (p = 0.006). The major reason for revision was a defect that was too large for the prescribed plate. Patients with large orbital defects needing surgical treatment are at risk of implant malposition. The orbital reconstruction with preformed plate evidences good outcome in single wall fractures. However, the risk of malposition increases massively with fracture size. We therefore postulate that in large, two-wall fractures, primary treatment with a PSI has to be considered.